Perineal Management: Confidence And Educational Needs Among Midwives In Selected Health Facilities In Mityana District, Uganda. A Descriptive Cross-Sectional Study. - Nakimuli, Jackline; Ihudiebube-Splendor Chichaodili N (Student’s Journal of Health Research Africa, 2021)
Background: Midwives are principal professionals providing woman-centered continuity of care for childbearing women worldwide. Perhaps there are inadequate pieces of evidence to infer whether there are differences in illness and deaths, usefulness, and psychosocial results between models of care that are midwife-led and other care models. Methodology: A descriptive cross-sectional study was used where a Self-administered and semi-structured questionnaire with both closed and open-ended questions was used to collect data. Results: The level of confidence in perineal management and managing vaginal deliveries is directly influenced by the level of education attained by the midwife. From the study findings, midwives who had attained a degree in midwifery expressed more confidence in perineal management and vaginal deliveries than those with a diploma and certificate in midwifery. Study findings also showed that midwives with the least time of exposure (work experience, those with fewer than a year of working experience expressed low levels of confidence towards perineal management and vaginal deliveries. Conclusions: The findings from this study demonstrate= that midwives crave additional educational opportunities in perineal management, especially, in prevention strategies. They demanded up-to-date evidence and best practice recommendations to provide guidance to midwifery perineal management. This shows that the midwives’ were enthusiastic about the continuous evaluation of their practices and commitments to life-long learning. It is therefore anticipated that midwives tailored educational program that will not only improve clinical skills and perineal protection techniques but also confidence in decision making be established to meet midwifery needs Recommendations: Midwives should embark on ‘back to basics approach, they should continuously review Anatomy and physiology, including the perineum and pelvic floor and mechanism of labor. This paucity of knowledge may be a consequence of the previously limited focus on the anatomy of the perineum in earlier pre-registration midwifery curricula and existing perineal management workshops.